Sound and space in Renaissance Venice architecture, music, acoustics - Howard, Deborah 1946-; Moretti, Laura 1969- (Yale Univ. Press, 2009)
Preface -- 1. introduction -- 2. San Marco -- 3. Island monasteries -- 4. Mendicant friaries -- 5. Parish churches -- 6. Opedali Grandi -- 7. General conclusions -- Appendices -- Bibliography -- Photo credits -- Glossary